The importance of non-tidal water-level variability for reconstructing Holocene relative sea level - Kemp, Andrew C. (2024)
Salt-marsh sediment is an important geological archive for reconstructing Holocene relative sea level. The vertical uncertainty of these reconstructions is usually quantified as proportional to tidal range, resulting in a presumed primacy of microtidal regions for generating precise records. We analyzed hourly water-level predictions and measurements over 1983e2001 from 43 tide gauges on the U.S. Atlantic coast to quantify the (1) relationship between elevation (relative to tidal datums) and duration of inundation; and (2) relative importance of astronomical tides and non-tidal (meteorological, hydrologic, and oceanographic) processes. Non-tidal processes are more likely to exert a proportionally large inf luence on water levels in regions with small astronomical tides, and less likely to do so where tides are large. In some microtidal regions (e.g., Chesapeake Bay), the precision of RSL reconstructions is likely overestimated, while in regions with large tidal range (e.g., Gulf of Maine) it may be underestimated. Adopting an inundation frequency rather than predicted astronomical datum for the upper limit of saltmarsh distribution may reduce this bias. Relative sea-level reconstructions often assume constant tidal range through time, but in some microtidal regions this assumption should be expanded to explicitly describe additional stationarity of non-tidal contributions.